Evaluation of cucumber (Cucumis sativus) germplasm for agronomic traits and disease resistance and estimation of genetic variability - RANJAN, PRAGYA; GANGOPADHYAY, K K; BAG, MANAS KUMAR; ROY, ANIRBAN; SRIVASTAVA, R; BHARDWAJ, R; DUTTA, M (The Indian Journal of Agricultural Sciences, 2015)
The material used in the present study is of diverse nature and can be used in the breeding programme for development of improved genotypes in cucumber (Cucumis sativus L.). The unique accessions identified in this study can be useful as genetic stocks. The superior genotypes for fruit trait variability combined with disease resistance may assist the breeders in identifying populations with desired traits for inclusion in crop improvement programme.